The Assessment Of The Effect Of Surface Roughness On Drag Coefficient And Aerodynamics Features Of Loggerhead Sea Turtle Carapace - Cheng, See Yuan; Mat Yamin, Ahmad Kamal; Chan, Alan Kah Poh; Jalaluddin, Ainil Jesita; Ishak, Iskandar Shah; Mansor, Shuhaimi (2008)
The present investigation primarily studies the effect of surface roughness on the drag coefficient, Cd of a Loggerhead sea turtle carapace using a subsonic wind tunnel. The pressure coefficient, Cp distribution across the Loggerhead carapace was also investigated and is compared to the Cp trend of an airfoil in order to deduce the aerodynamics features of the Loggerhead carapace. One-to-five-scaled models are created based on the dimensions of a real Loggerhead turtle with simplification. Four roughness scales were employed to capture the Cd trend at increasing Reynolds numbers, Re. As expected, the Cd levelled off with Re for all four models investigated. However, the Re where constant Cd began varies with relative roughness of the carapace models. The results also show good correlation between the Cd and relative roughness. In addition, the wind tunnel results are able to capture the Cp trend of the carapace models and compared to Cp values of an airfoil. Results reveal that the upper surface of the Loggerhead carapace is streamlined but with restrictions of angle of attack.